Central banking today in the Eastern Caribbean. - Lewis, Lucilla (1991)
Discusses some of the reasons for more flexibility in the use and effectiveness of monetary policy in the ECCB area. Points to means by which the ECCB can achieve its goals while safeguarding itself from balance of payments crises and other instabilities that may arise in the financial system.